A learning process within an education research group: an approach to learning qualitative research methods - Hernández-Hernández, Fernando; Sancho-Gil, Juana M. (International journal of social research methodology, 2015)
This paper builds on the history of Esbrina, an established research group in Spain with almost 20 years' experience and a deeply-rooted tradition of self-reflection and learning. We start by analysing the academic and social contexts in which the group was created and recognised. We make explicit team members' backgrounds, dispositions and positionalities, to provide insight into the tensions aroused in deciding research topics, methodological approaches and research methods. Then we focus on two specific projects and explore the learning processes of those engaged in them: the first involves micro-ethnography, for which we examine our apprenticeship process through interviews, observation, inferential analysis and visual documentation. The second involves collaborative ethnography, for which we give an analytical account of how we created different ways of learning through collaborating and narrating. Throughout the paper, we reflect on our determination to create a methods-learning environment in which we constantly challenge our comfort zone by trying to do research on topics involving authentic learning. The most innovative aspect of the process is that senior and junior researchers, including group directors, play both the role of teachers and learners.